EDUKASI KESEHATAN DALAM UPAYA MEWUJUDKAN GENERASI SEHAT BEBAS STUNTING (GENSEBES) - Jamhariyah; Kiswati; Sugijati; Awaliyah T, Fitrah Hadiyati (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Teenagers are the next generation of a nation, who are expected to be the bearers of the baton of a country's development in achieving national prosperity. Health issues are very important, especially for teenagers. Many adolescent nutritional problems occur due to incorrect nutritional behavior, such as an imbalance between nutrition and recommended nutritional adequacy. Lack of energy and protein affects the body, resulting in obesity, chronic energy deficiency (malnutrition) and anemia. A preliminary study through an initial examination of 17 female adolescents at MA Yasrama, found that 2 people (11.7%) had severe anemia, 11 people (64.7%) had moderate anemia and 4 people (23.5%) had mild anemia. Apart from that, there were 8 teenagers who were classified as thin and had a height of <150 cm. The purpose of implementing this Community Service (PKM) activity is to create teenagers who care about their own health, are responsive to unhealthy behavior and are able to prevent and overcome their health problems independently so that the health level of teenagers can improve. This is done through activities to identify health problems in adolescents, education and assistance regarding healthy living behavior in adolescence as well as peer training and at the end of the activity, monitoring and evaluation of the results of these activities are carried out. This community service activity was carried out from April 2024 to September 2024, involving 30 female youth participants at MA Yasrama, Baratan Village, Jember Regency.